The construction process of precast reinforced concrete of frame structure for Industrialised Building System (IBS) / Muhammad Aminuddin Kamarul Zaman - Kamarul Zaman, Muhammad Aminuddin (Universiti Teknologi MARA, Perak, 2019)
This report briefly described the construction process of precast reinforced concrete (PRC) frame structure focused on beam components. To achieve aimed of this report, two objectives were carried to determine the construction process of precast reinforced concrete of frame structure for IBS that focused on precast RC beams components. The construction work process was deliberated in production, transportation and installation aspects. On the other hand, problems and solution during the process of precast RC beams was also explained. The results revealed that the production, transportation and installation work process of precast reinforcement concrete beam for industrialised building system have been determined. Moreover, the problems and solutions occurred on site have been identify. In conclusion, by implement the IBS in construction nowadays, it can give better quality environment, rapid construction period and reduced waste in a large amount compared to the conventional construction method.